2023
DOI: 10.3390/ijms24065098
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Inhibitors Reduce PCSK9 and Early Atherogenic Biomarkers in Stimulated Human Coronary Artery Endothelial Cells

Abstract: Despite reports on the efficacy of proprotein convertase subtilisin-Kexin type 9 (PCSK9) inhibitors as a potent lipid-lowering agent in various large-scale clinical trials, the anti-atherogenic properties of PCSK9 inhibitors in reducing PCSK9 and atherogenesis biomarkers via the NF-ĸB and eNOS pathway has yet to be established. This study aimed to investigate the effects of PCSK9 inhibitors on PCSK9, targeted early atherogenesis biomarkers, and monocyte binding in stimulated human coronary artery endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…According to published methods, 10 mmol/L β-gp, 20ug/m dexamethasone and 50ug/mL Lascorbic acid were added to the routine medium to induce osteogenesis of VSMCs for 7 days, the medium were changed every 2/3 days [23][24][25][26][27][28] . To mimic the effects of PCSK9i in vivo, 100 µg/mL of reagent-grade puri ed evolocumab (Selleck, America) was used to co-incubate with VSMCs for 7 days during osteogenesis induction [29][30][31] . To mimic the stimulation of VSMCs by PCSK9 protein in vivo, refer to previous research [32] , 0 µg/ml, 0.55 µg/ml, 1.1 µg/ml, 2.2 µg/ml, and 4.4 µg/ml of recombinant human PCSK9 (MedChemExpress, USA) were co-incubated with VSMCs for 7 days, and the concentration exhibiting the highest intracellular calcium content was chosen for subsequent experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…According to published methods, 10 mmol/L β-gp, 20ug/m dexamethasone and 50ug/mL Lascorbic acid were added to the routine medium to induce osteogenesis of VSMCs for 7 days, the medium were changed every 2/3 days [23][24][25][26][27][28] . To mimic the effects of PCSK9i in vivo, 100 µg/mL of reagent-grade puri ed evolocumab (Selleck, America) was used to co-incubate with VSMCs for 7 days during osteogenesis induction [29][30][31] . To mimic the stimulation of VSMCs by PCSK9 protein in vivo, refer to previous research [32] , 0 µg/ml, 0.55 µg/ml, 1.1 µg/ml, 2.2 µg/ml, and 4.4 µg/ml of recombinant human PCSK9 (MedChemExpress, USA) were co-incubated with VSMCs for 7 days, and the concentration exhibiting the highest intracellular calcium content was chosen for subsequent experimental procedures.…”
Section: Methodsmentioning
confidence: 99%
“…According to published methods, 10 mmol/L β-gp, 20ug/m dexamethasone and 50ug/ mL L-ascorbic acid were added to the routine medium to induce osteogenesis of VSMCs for 7 days, the medium were changed every 2/3 days (24-29). To mimic the effects of PCSK9i in vivo, 100 μg/mL of reagent-grade purified evolocumab (Selleck, America) was used to co-incubate with VSMCs for 7 days during osteogenesis induction (30)(31)(32). To mimic the stimulation of VSMCs by PCSK9 protein in vivo, refer to previous research (33), 0 μg/mL, 0.55 μg/mL, 1.1 μg/mL, 2.2 μg/mL, and 4.4 μg/mL of recombinant human PCSK9 (MedChemExpress, USA) were co-incubated with VSMCs for 7 days, and the concentration exhibiting the highest intracellular calcium content was chosen for subsequent experimental procedures.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%
“…The in vitro study by authors Zulkapli et al showed that the co-incubation of alirocumab and evolocumab at specific concentrations resulted in an upregulation of the production of the eNOS protein. Only evolocumab caused an increase, although not significant, in eNOS mRNA [ 75 ]. Treatment with a PCSK9 inhibitor given to type 2 diabetes (T2D) patients (110 individuals) along with SGLT2i treatment improved FMD and the bioavailability of NO.…”
Section: Endothelial Dysfunction Markers and Pcsk9 Inhibitorsmentioning
confidence: 99%